Osteossíntese minimamente invasiva com placa bloqueada nas fraturas de tíbia em cães - Rosa-Ballaben, Nátalie Massaro [UNESP] (2014)
Advances in the comprehension of the bone healing and complications of the treatment of the fractures have been changed some concepts. Less invasive procedures have been advocated. A minimally invasive plate osteosynthesis (MIPO) is one of the best ways to avoid over tissue damage. The aim of this study was to evaluate the use of MIPO in tibial fractures in dogs. Ten dogs presenting a tibial fracture were used. Deambulation, swelling intensity and radiographic changes were evaluated preoperatively, just after the procedure and at 15, 30, 60, 90 e 120 days postoperatively. Six of 10 (60%) dogs were able to walk at 15 days postoperatively with slight swelling and mild lameness. Two of 10 (20%) presented normal walking at the same period. At 30 days postoperatively all dogs were able to walk normally. Six of them were not lame and 9 did not present swelling. Bone healing could be followed by radiographic evaluation. All dog presented initial radiographic signs of bone healing after 15 days postoperatively. Two of 10 showed clinical union at this time. In five of 10 (50%) clinical union could be observed after 60 days. The treatment of tibial fractures by MIPO is an effective alternative resulting in early and effective clinical union and can be performed without the use of image intensifiers